Prevalence and correlates of relapse in adult male patients with alcohol dependence: a cross sectional study conducted in a tertiary care hospital in Northern India - Kumar, Prashant; Thadani, Anupriya (International Journal of Advances in Medicine, 2022)
Background: Relapse to alcohol dependence after successful detoxification and rehabilitation is a public health concern worldwide. Although the burden of alcohol dependence is massive in the Indian subcontinent, very little is known about the causes of relapse among patients treated for alcohol abuse. Hence, this study was designed to evaluate the prevalence and factors associated with relapse in patients of alcohol dependence disorder. Methods: 50 male patients diagnosed with alcohol dependence (according to ICD-10 criteria) who attended both in-patient and out-patient outpatient department (OPD) of a tertiary care hospital were included in our study. Severity of Alcohol Dependence Questionnaire (SADQ) for severity of alcohol dependence, Presumptive Stressful Life Events Scales (PSLES) and relapse precipitant inventory were used for correlation of factors responsible for relapse amongst these alcohol abusers after informed consent and acquiring socio-demographic details. Results: Out of 50 patients enrolled in the study as per the International Classification of Diseases 10th revision Diagnostic Criteria for Research (ICD-10 DCR), a majority (92%) were Hindus, 60% belonging to the rural background. Family history of alcohol dependence was found to be present among 46% patients, and a majority had moderate to severe alcohol dependence. Craving for alcohol was found to be the most common cause of relapse amongst these, and 72% patients showed moderate to severe stress on the PSLES scale. Conclusions: Alcohol consumption is emerging as a major public health problem in India. Regular follow up with family, peer and social support are essential along with vocational rehabilitation to prevent relapse. Multi-centric scientific community-based research studies have to be conducted in various individual states to understand the problem better. There is a dire need for various policymakers, media, professionals and society to come together and create awareness about the consequences of chronic alcohol through sensitization programmes and health education campaigns.